VD_FINDINFO HC / 2012 / 622 vom 3. Oktober 2012 - VD Tribunal cantonal (2012)
TRANSACTION JUDICIAIRE, ERREUR ESSENTIELLE | 140 CC, 23 CO, 24 CO, 241 al. 2 CPC (CH), 241 CPC (CH), 279 al. 2 CPC (CH), 279 CPC (CH)